Habilidades sociales de los docentes para mejorar la gestión educativa de la institución “Víctor Manuel Ciudad Ávila” del Puerto de Malabrigo, distrito de Rázuri – Ascope 2016 - Alva Muñoz, Miguel Angel (2019)
ABSTRACT The objective of the research was to demonstrate that with the application of the Social Skills Program of teachers significantly improve the Educational Management of the Educative Institution "Víctor Manuel Ciudad Ávila" from the Port of Malabrigo, district of Rázuri - Ascope 2016. The research is quantitative, of pre - experimental design, with a non - probabilistic sample of twenty teachers, using the Hypothetical - Deductive method for its development, using a questionnaire with forty - five items. Chi Square was used (X2), to check the hypothesis, as well as the Pearson Correlation Coefficient, with a level of significance at 1% and a level of confidence at 99%. Significantly improved the Educational Management in the teachers of the I.E. "Víctor Manuel Ciudad Ávila" Malabrigo - Ascope 2016, advancing from the "MALO" level with an average score of 2.00 at the "GOOD" level with an average score of 54.00 points. In the Communication dimension, it was significantly improved by advancing from the "BAD" level with an average score of 19.00 points at the "GOOD" level with an average score of 55.00 points, and with an existing correlation of (0.75). In the Flexibility dimension, he progressed significantly from the "BAD" level with an average score of 19.00 at the "GOOD" level with 54.00 points, and with an existing correlation of (0.85). In the Teamwork dimension, he advanced from the "BAD" level with an average score of 22.00 at the "GOOD" level with an average score of 52.00 and with an existing correlation of (0.73).